2022
DOI: 10.3390/jcm11051362
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Levels of SIRT1 and SIRT3 Correlate with Severity of Skin and Lung Fibrosis and Peripheral Microvasculopathy in Systemic Sclerosis

Abstract: Systemic sclerosis (SSc, scleroderma) is a severe autoimmune connective tissue disease characterized by widespread peripheral microvasculopathy, and progressive cutaneous and visceral fibrosis, leading to significant organ dysfunction. Sirtuins (SIRTs) are a family of NAD-dependent protein deacetylases with pleiotropic effects on a variety of biological processes, including metabolism, cell survival, and aging. In the last decades, increasing studies have explored the contribution of SIRTs to the pathogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…Among the seven SIRT isotypes (SIRT1–SIRT7), SIRT1, SIRT6, and SIRT7 are mainly nuclear, while others are mostly cytoplasmic (SIRT2) or mitochondrial (SIRT3, SIRT4, and SIRT5) [ 125 ]. Since SIRT1 and SIRT3 have recently emerged as noteworthy players in regulating angiogenesis [ 126 , 127 , 128 ], our group recently conducted a study in order to evaluate the association of these circulating deacetylases with the severity of SSc-related peripheral microvascular damage [ 129 ]. In this study, we provided the evidence that serum levels of both SIRT1 and SIRT3 are decreased in SSc patients compared to healthy controls and that their decrease correlated with the severity of NVC abnormalities, with SIRT3 also being related to the occurrence of ischemic DUs.…”
Section: Sirtuinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the seven SIRT isotypes (SIRT1–SIRT7), SIRT1, SIRT6, and SIRT7 are mainly nuclear, while others are mostly cytoplasmic (SIRT2) or mitochondrial (SIRT3, SIRT4, and SIRT5) [ 125 ]. Since SIRT1 and SIRT3 have recently emerged as noteworthy players in regulating angiogenesis [ 126 , 127 , 128 ], our group recently conducted a study in order to evaluate the association of these circulating deacetylases with the severity of SSc-related peripheral microvascular damage [ 129 ]. In this study, we provided the evidence that serum levels of both SIRT1 and SIRT3 are decreased in SSc patients compared to healthy controls and that their decrease correlated with the severity of NVC abnormalities, with SIRT3 also being related to the occurrence of ischemic DUs.…”
Section: Sirtuinsmentioning
confidence: 99%
“…In this study, we provided the evidence that serum levels of both SIRT1 and SIRT3 are decreased in SSc patients compared to healthy controls and that their decrease correlated with the severity of NVC abnormalities, with SIRT3 also being related to the occurrence of ischemic DUs. Of note, via logistic regression analysis, we further demonstrated that, between the two SIRTs, SIRT3 may better mirror peripheral vascular disease activity and severity [ 129 ].…”
Section: Sirtuinsmentioning
confidence: 99%
“…Wei et al showed that the pro-fibrotic effect of TGFβ was diminished by activation of SIRT1, while Zerr et al showed downregulate of SIRT1 diminished TGFβ/Smad signaling ( 117 , 118 ). More recently, Manetti et al measured circulating SIRT1 and SIRT3 levels in a cohort of SSc patients and healthy controls, and found significantly decreased serum levels of both SIRT1 and SIRT3, as well as an association with the extent of skin involvement ( 127 ). Further, Akamata et al revealed that SIRT3 activity was significantly reduced in SSc biopsies and that its activation can augment TGFβ signaling and the fibrotic response ( 123 ).…”
Section: Wound Healingmentioning
confidence: 99%
“…Finally, SIRT7 may inhibit fibroblast migration. both SIRT1 and SIRT3, as well as an association with the extent of skin involvement (127). Further, Akamata et al revealed that SIRT3 activity was significantly reduced in SSc biopsies and that its activation can augment TGFβ signaling and the fibrotic response (123).…”
Section: Human Disease Models and Clinical Applicationsmentioning
confidence: 99%
“…A link between unresolved inflammation and features of EMT during fibrogenesis in hypertrophic scar tissue has been suggested, with an increased expression of the mesenchymal marker FSP1 observed along with the EMT proteins SNAIL2 and TWIST [93]. Interestingly, decreased SIRT1 and SIRT3 serum levels have been measured in scleroderma patients compared to controls [94]. Moreover, SIRT1 has been shown to reduce skin fibrosis through TGFβ/Smad3 inhibition [95].…”
Section: Fibrosismentioning
confidence: 99%